PERBANDINGAN PENGGUNAAN DUA BUAH JENIS ZAT ADITIF TERHADAP EMISI GAS BUANG PADA SEPEDA MOTOR 4 LANGKAH - Priyanto, Teguh; Budiyono, Budiyono; Prasetyo, Imam (Surya Teknika : Jurnal Ilmiah Teknik Mesin, 2021)
Motor vehicles used to support human life have a negative effect on air quality. Motor vehicle exhaust contains hazardous substances, including carbon monoxide (CO) and hydrocarbons (HC). Therefore, several kinds of additives emerged to reduce vehicle exhaust emissions, these additives include Eco Racing and Salvis Fuel Additive. In this study, the author tries to examine how the effect of the use of the two additives is to reduce CO and HC gas levels in motor vehicles and compare the test results of the two additives. The test was carried out in three stages, namely testing with 100% pure pertalite fuel, pertalite with a mixture of Eco Racing 1 grain and pertalite with a mixture of Salvis Fuel Additive 1 ml with variations in rotation of 1500 rpm, 2000 rpm, 2500 rpm, 3000 rpm, 3500 rpm, 4000 rpm, 4500 rpm and 5000 rpm. The test is carried out 3 times at each engine speed for maximum results.The results of the test show that the mixture of pertalite with Eco Racing 1 grain is the best in reducing CO and HC gas levels, which is 0.63% for CO levels at 3500 rpm and 37 ppm for HC levels at 3500 rpm.Keywords : Exhaust Emissions, Eco Racing, Salvis Fuel Additive